Seasonal Monitoring of Ocean Parameter Over Green Mussel Cultivation area in West Part of Cirebon Seawater - Mochamad Riam Badriana; Ashadi Arifin Nur; Arsy Ilham Hidayatullah; Abi Widyananto Prastyo; Lamona Imudyati Bernawis; Chungkyun Jeon; Ivonne Milichristi Radjawane; Hansan Park (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
West part of Cirebon in the past suffered an extraordinary event due to poisonous food found in green mussel. It is necessary to monitor current water quality over this region since this area still used for green mussel cultivation area. In-situ measurement and laboratory analysis were done to monitor the condition of seawater around Gunungjati as part of green mussel cultivation area in Cirebon regency. Several points had been measured through CTD Valeport Midas+ in prior to measure physical (temperature, salinity, pH, chlorophyll-a, turbidity) and chemical seawater (dissolved oxygen, Nitrate, Orthophosphate, Hg, Pb, Cd concentration) characteristics, meanwhile water sample had been brought to laboratory to be checked its heavy metal concentration. Additionally, past study and data related to green poison event in Cirebon was taken account into observation and analysis. Seasonal result show slightly different value though vertical distribution data where temperature (30.1°–32.3°C), salinity (26.9–32.0 psu), and pH (7.5–8.7) are high in December but lower in July, meanwhile, chlorophyll-a (0.2–20.9 mg.L-1), dissolved oxygen (0.2–7.8 mg.L-1), and turbidity (1.3–20.1 NTU) are increasing in October. Nitrate and orthophosphate concentration find in water sample is 0.097–0.537 mg.L-1 and <0.01–0.32 mg.L-1, respectively. Parameters of Cd (<0.001 mg.L-1), Hg (<0.00014 mg.L-1), and Pb (<0.001 mg.L-1) are still below the threshold. The condition of seawater of west part of Cirebon or at cultivation area is still in moderate condition based on the national standard. Although, turbidity and dissolved oxygen is still above the standard quality.